2021
DOI: 10.3390/su131911029
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Soil Colour to Estimate Soil Organic Carbon Using a Large-Scale Citizen Science-Based Approach

Abstract: Rapid, low-cost methods for large-scale assessments of soil organic carbon (SOC) are essential for climate change mitigation. Our work explores the potential for citizen scientists to gather soil colour data as a cost-effective proxy of SOC instead of conventional lab analyses. The research took place during a 2-year period using topsoil data gathered by citizen scientists and scientists from urban parks in the UK and France. We evaluated the accuracy and consistency of colour identification by comparing “obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…In our study, air-dry samples were analysed because the drying of soil enlarges the span of both value and chroma (Pretorius et al 2017;Rubinić et al 2021). Of the three colour variables, value and chroma show to be strongly dependent on the SOM content (Konen et al 2003;Pretorius et al 2017;Jorge et al 2021). In turn, the relationship between SOM and hue is weak (Pretorius et al 2017;Jorge et al 2021).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In our study, air-dry samples were analysed because the drying of soil enlarges the span of both value and chroma (Pretorius et al 2017;Rubinić et al 2021). Of the three colour variables, value and chroma show to be strongly dependent on the SOM content (Konen et al 2003;Pretorius et al 2017;Jorge et al 2021). In turn, the relationship between SOM and hue is weak (Pretorius et al 2017;Jorge et al 2021).…”
Section: Discussionmentioning
confidence: 97%
“…Many articles discuss dependences between the colour of soils and the content of soil organic matter (SOM) or organic carbon (C org. ) (Blume and Helsper 1987;Evans and Franzmeier 1988;Łachacz 1993;Schulze et al 1993;Konen et al 2003;Wills et al 2007;Jorge et al 2021), nitrogen (Qian et al 1993;Moritsuka et al 2014) and iron oxides (Leger et al 1979;Torrent et al 1983;Schwertmann 1993;Moritsuka et al 2014). A rapid assessment of the SOM content using Munsell soil colour charts can help to determine trends and consequently the soil degradation state (Minh et al 2020;Rubinić et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the place of only being valued as modes of community engagement, cultural geographers are increasingly working as collaborators within large teams of scholars and other stakeholders, addressing complex challenges. Research in this vein ranges from Hilary Geoghagen and colleagues' work on tree health and biodiversity (Ferrando Jorge et al, 2021), to Gail Davies, Beth Greenhough and colleagues' work on science, health and animal welfare (Davies et al, 2020). The work of Chile based 'BioGeoArt', GeoHumanities and Biogeography Group is an excellent cultural geography led example of the scale and potential of these ways of working.…”
Section: Into the Critical Zone 2: Life Crisis And Lossmentioning
confidence: 99%
“…As a result, they studied dirty and old Munsell charts and they found that the prediction accuracy could be reduced due to the noise in the samples. In [8], the authors used spectroscopy and compared the results with observed MCC estimates in order to ensure robustness in the process of observation and data collection. They detected a certain correlation between the spectrophotometer and the observed measures.…”
Section: Introductionmentioning
confidence: 99%